2019
DOI: 10.1093/ptj/pzz154
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of the Short Physical Performance Battery for Detecting Frailty in Older People

Abstract: Background The Short Physical Performance Battery (SPPB) is widely used to predict negative health-related outcomes in older adults. However, the cutoff point for the detection of the frailty syndrome is not yet conclusive. Objective The aim of this study was to determine the diagnostic value of the SPPB for detecting frailty in community-dwelling older adults. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
9

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 31 publications
2
62
0
9
Order By: Relevance
“…We performed the assessment of SPPB in the current study, which is widely used in geriatric medicine to assess frailty, sarcopenia, and lower extremity function in older persons 35,36,37 . The results have shown that only 22% of all stroke patients at baseline and 43% of patients after a 4‐week FU were able to perform the test.…”
Section: Discussionmentioning
confidence: 99%
“…We performed the assessment of SPPB in the current study, which is widely used in geriatric medicine to assess frailty, sarcopenia, and lower extremity function in older persons 35,36,37 . The results have shown that only 22% of all stroke patients at baseline and 43% of patients after a 4‐week FU were able to perform the test.…”
Section: Discussionmentioning
confidence: 99%
“…It has primarily been used to assess elderly patients in the hospital, clinical and community settings. The SPPB test might be also used as a screening tool to detect frailty syndrome in community dwelling older adults [214,215]. The SPPB test consists of three assessments: repeated chair stands, balance tests (side-by-side, semi-tandem and tandem balance tests) and eight-foot walk (2.44 m) test [213].…”
Section: Short Performance Physical Batterymentioning
confidence: 99%
“…Physical performance The SPPB is a useful screening tool for identifying poor physical performance and frailty syndrome in the elderly population. [27] The SPPB score only objectively measures lower limb physical performance but also is highly associated with adverse health outcomes such as fall risk, disability, and mortality, even in high-functioning older adults. [28] It consists of three tests, including standing balance, gait speed in a 4-m walk, and a timed test of 5 repeated chair stands.…”
Section: Frailtymentioning
confidence: 99%